INFLUÊNCIA DA APLICAÇÃO DE BIOFERTILIZANTE NOS ATRIBUTOS FÍSICO DE SOLO EM DIFERENTES SISTEMAS DE MANEJO - RAMOS NASCIMENTO, MARYANNE; VIEIRA DOS SANTOS, WESLEY; DA SILVA MENEZES, RONIEDISON; SPANACHUKI, ELÓI; VILALBA MARTINS, JENNIFER CAROLINE; FANAIA DA CRUZ, ELIANAY (ANAIS DO ENIC, 2025)
-